Production and Growth of Soybean on Water Hyacinth Bokashi Giving with Two Activators Types - Asrijal, Asrijal; Upe, Ambo; Rahmawati, Rahmawati; Sulfiani, Sulfiani; Aslidayanti, Dan (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study aimed to determine the production and growth of soybean on water hyacinth bokashi giving with two activators types. The study was conducted in Leweng Village, TakkalallaSubdistrict, Wajo District. The method used was Randomized Block Design (RBD), consisting of three (3) treatments, namely Bokashi (b0), Bokashi 2 tha-1 with Activator EM4 (b1), and Bokashi 2 tha-1 with Activator Tadabur (b2). Each treatment was repeated three times so that the number of treatment combinations was 9 combinations (9 plot treatment). The results show that the average soybean production per hectare application of water hyacinth bokashi with EM4 activators is 0.80 tons per hectare, while the application of water hyacinth bokashi with Tadabur activists is 0.79 tons per hectare. The application of water hyacinth bokashi with EM4 activators is much better, compared to water hyacinth bokashi with activist Tadabur.